Hepatitis in Dengue Shock Syndrome - Luiz José de Souza; Helder Gonçalves Carneiro; João Tadeu Damian Souto Filho; Thiago Ferreira de Souza; Vitor Azevedo Côrtes; Carlos Gicovate Neto; Diogo Assed Bastos; Edno Wallace da Silva Siqueira (Brazilian Journal of Infectious Diseases)
Dengue fever is the most frequent arbovirus disease in the world and the most important one in terms of morbidity and mortality. Atypical manifestations of dengue have become commonplace during the last few years, including hepatic damage, which manifests mainly by pain in the right hypochondrium and an increase in the levels of aminotransferases. We describe a case of acute hepatitis in a patient with Dengue Shock Syndrome Grade III. We analyzed the clinical and laboratory aspects of this atypical complication of dengue as well as the differential diagnoses.